The rule is
+-= -
--=-
-+= -
++=+
S0: -6 + -8
-6 - 8, which equals -14.
six plus negative eight is two
The sum is negative 8.
-6 + 8 is the same as 8 - 6 is 2
8+6+(-3) =14+(-3) =11
-6 + +8 = +2
six plus negative eight is two
The sum is negative 8.
-6 + 8 is the same as 8 - 6 is 2
8+6+(-3) =14+(-3) =11
-6 + +8 = +2
9
-2
8 + -2 = 6 SIX. It is as if you are saying 8 minus two which equals 6. A negative is a minus.
-14
it will be -13 because -5 +-8 its like adding negative plus a negative equals a negativeexample:-6+-2=-8 but be careful because if its -6+2=4 because now you are subtracting
Minus a negative means you can plus a positive so therefore the answer would be positive 8.
4/8 + (-6) = 1/2 - 6 = -51/2